Factors contributing to low uptake of cervical cancer screening among women living with Human Immunodeficiency Virus at Queen Elizabeth II Hospital, Lesotho - Sejana, Bonang (My University, 2024)
BACKGROUND Cervical cancer is a public health concern as a vast number of women are dying of it in Southern Africa. The study embarked on factors related to the low numbers of women screening for cervical cancer among women living with HIV as they are at increased risk of developing it. The utilisation of services seems low, although diagnosis and mortality rate continue to be high. METHOD A quantitative cross-sectional study was conducted at Queen Elizabeth II Hospital in Maseru, Lesotho. Though cross-sectional studies are valuable for identifying potential relationships between variables, it's important to note that they cannot establish causality. Correlation does not imply causation, and other factors or variables not accounted for in the study may influence the observed relationships. A questionnaire was administered to 346 women living with HIV impending for their clinical services at Queen Elizabeth II Hospital were enrolled in the study. Data was analysed using SPSS V22. The following analyses were employed, descriptive, inferential statistics and logistic regression. RESULTS Sociodemographic data shows majority of study participants were between 30 and 34 years old, married, and had attained secondary qualifications. In addition, the data shows that women were cognisant of screening services for cervical cancer at Queen Elizabeth II Hospital. The chi-square test indicates a significant association between married participants and cervical cancer awareness (p-value < 0.001). The odds of being aware of cervical cancer are 1.43 times higher for individuals who are married compared to those who are not married. CONCLUSION A high percentage of knowledge on screening for cervical cancer among women taking ART in this facility might be credited to the fact that the screening has been integrated into routine ART services. Furthermore, marital status, age and living in urban areas are sociodemographic variables linked to knowledge or awareness of cervical cancer screening services. Therefore, more emphasis and exploration can be placed on rural areas to strengthen and cascade knowledge and awareness among populations.
Thesis (MPH.) -- University of Limpopo, 2024
Keywords: Low uptake; Cervical cancer screening; Women living with HIV; Lesotho; Cervix uteri -- Cancer; HIV infections -- Lesotho; HIV-positive women